Avaliação por microtração de restaurações diretas com resina bulk-fill flow em dentes com diferentes condicionamentos da dentina - Wagner, Larissa (2022)
The aim of this study was to evaluate the microtensile bond strength of direct restorations with bulk-fill flow resin in endodontically treated teeth that received different types of dentin conditioning. Thirty upper and lower first molars were used. The samples were randomly divided into 3 groups, which were prepared with EDTA as the final irrigant and bulk-fill flow resin as the restorative material, differing only in the type of etching received (G1- phosphoric acid 37% + primer + adhesive; G2 - self-etching adhesive ; G3- primer + adhesive). Subsequently, the prepared teeth were cut, obtaining 41 tooth-resin sticks in total. The specimens were subjected to tensile loading in a Universal testing machine at a speed of 0.5 mm/min, the maximum fracture load (in N) was recorded and the bond strength (MPa) calculated. Subsequently, the failure mode was evaluated using light microscopy. Thus, there was a significant difference between the groups. Group 1 (conventional adhesive system) was more resistant than group 2 (self-etching), between group 1 and group 3 (conventional without phosphoric acid) there was no significant difference, as well as between group 2 and group 3. Adhesive-type failure mode was prevalent in all groups. It was concluded that the different types of dentin conditioning in restorations with bulk-fill flow resin after endodontic treatment influenced the microtensile bond strength. The conventional 3-step adhesive system was more resistant when compared to the self-etching adhesive system. On the other hand, etching dentin with EDTA alone had the same bond strength as when using 37% phosphoric acid.